A multi-scale aqueous dispersion coating technique for manufacturing carbon fiber reinforced PEEK composite. (February 2023) - Balakumaran, V.; Alagirusamy, Ramasamy; Kalyanasundaram, Dinesh
Abstract: Carbon fiber (CF)/PEEK composites were manufactured using towpregs impregnated with PEEK microparticles via an in-house developed dispersion coating method. The PEEK microparticles were dispersed in a self-stabilized aqueous solution of Polyimide (PI) precursor polyamic acid ammonium salt solution (PAAS). The dispersion coating produced a uniform coating of PEEK microparticles on the surface and along the cross-section of CF tow to overcome the low melt flow of PEEK, a high-performance thermoplastic. The PAAS formed a layer of PI nanoparticles on CF acting as an interface between CF and PEEK in the composite. The composites yielded a flexural strength of ∼1160 MPa; tensile strength of ∼1900 MPa; compressive strength of ∼600 MPa; interlaminar shear strength of ∼70 MPa and free of void evident from micro-CT and microstructure evaluations. A detailed physiochemical study of the dispersion, coated tow and composite are provided to understand the mechanism of the dispersion coating process.